1991
DOI: 10.1128/jvi.65.5.2237-2244.1991
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of activation of the Epstein-Barr virus productive cycle

Abstract: The promoter for the 2.8-kb RNA of Epstein-Barr virus encoding BZLF1 and BRLF1 was identified and shown to be activated by both BZLF1 and BRLF1 but not by 12-0-tetradecanoylphorbol-13-acetate. Site-directed mutagenesis suggests that two binding sites for BZLF1 within the promoter contribute to the transactivation by BZLF1. The early kinetics of induction of the 2.8and 1.0-kb RNAs encoding BZLF1 and BRLF1 in Akata cells treated with anti-immunoglobulin indicate that both RNAs appear within 60 min. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
60
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(62 citation statements)
references
References 36 publications
1
60
1
Order By: Relevance
“…These observations suggested that both proteins have redundant properties. An additional level of complexity stems from the observation that the BZLF1 protein activates the promoters of BZLF1 and BRLF1 and, vice versa, the BRLF1 gene product up‐regulates the expression of the BZLF1 gene (Sinclair et al ., 1991; Ragoczy et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggested that both proteins have redundant properties. An additional level of complexity stems from the observation that the BZLF1 protein activates the promoters of BZLF1 and BRLF1 and, vice versa, the BRLF1 gene product up‐regulates the expression of the BZLF1 gene (Sinclair et al ., 1991; Ragoczy et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…BRLF1 is translated from a bicistronic mRNA which also encodes another IE gene product, BZLF1 (12,20). These two EBV gene products function in activating expression from a number of viral (3,5,8,13,15,18,28) and perhaps cellular (7) promoters, thereby initiating the lytic cascade. However, HVS R RNA is expressed as an early transcript in HVS-infected cells (23,25).…”
mentioning
confidence: 99%
“…Besides transcriptional control, Zta is regulated by posttranslational modifications such as phosphorylation (8), cellular localization (3), and protein-protein interactions (13,17,18,42,51). Zta can be translated from two different transcripts starting in either the BZLF1 or BRLF1 promoter (22,41), the latter giving rise to the expression of a bicistronic message coding for both Zta and Rta. Both transcripts are localized in a region covered also by the intron of the EBNA1 primary transcript.…”
mentioning
confidence: 99%